George H. Stuart papers - Stuart, George H. (George Hay), 1816-1890.
Correspondence, clippings, printed matter, scrapbook, illustrations, photographs, and other papers relating to the United States Christian Commission, of which Stuart was an organizer and leader; and letters of historical or autograph interest representing political and military leaders of the Civil War period.
Businessman, evangelist, and collector of autographs.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index to the correspondence available in the Library of Congress Manuscript Reading Room.
Keywords: United States. -- Army -- Supplies and stores; United States Christian Commission; Politicians -- United States -- Correspondence; United States -- Armed Forces -- Officers -- Correspondence; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Autographs; United States -- History -- Civil War, 1861-1865 -- Civilian relief; United States -- History -- Civil War, 1861-1865 -- War work; Businessmen; Collectors, Autograph; Evangelists